Screening for insulinoma antigen 2 and zinc transporter 8 autoantibodies: a cost‐effective and age‐independent strategy to identify rapid progressors to clinical onset among relatives of type 1 diabetic patients. (3rd December 2012) - Gorus, F. K.; Balti, E. V.; Vermeulen, I.; Demeester, S.; Van Dalem, A.; Costa, O.; Dorchy, H.; Tenoutasse, S.; Mouraux, T.; De Block, C.; Gillard, P.; Decochez, K.; et al.
Summary In first‐degree relatives of type 1 diabetic patients, we investigated whether diabetes risk assessment solely based on insulinoma antigen 2 (IA‐2) and zinc transporter 8 (ZnT8) antibody status (IA‐2A, respectively, ZnT8A) is as effective as screening for three or four autoantibodies [antibodies against insulin (IAA), glutamate decarboxylase 65 kDa (GAD) glutamate decarboxylase autoantibodies (GADA) and IA‐2A with or without ZnT8A] in identifying children, adolescents and adults who progress rapidly to diabetes (within 5 years). Antibodies were determined by radiobinding assays during follow‐up of 6444 siblings and offspring aged 0–39 years at inclusion and recruited consecutively by the Belgian Diabetes Registry. We identified 394 persistently IAA+, GADA+, IA‐2A+ and/or ZnT8A+ relatives (6·1%). After a median follow‐up time of 52 months, 132 relatives developed type 1 diabetes. In each age category tested (0–9, 10–19 and 20–39 years) progression to diabetes was significantly quicker in the presence of IA‐2A and/or ZnT8A than in their joint absence (P < 0·001). Progression rate was age‐independent in IA‐2A+ and/or ZnT8A+ relatives but decreased with age if only GADA and/or IAA were present (P = 0·008). In the age group mainly considered for immune interventions until now (10–39 years), screening for IA‐2A and ZnT8A alone identified 78% of the rapid progressors (versus 75% if positive for ≥ 2 antibodies among IAA, GADA, IA‐2A and ZnT8A or versus 62% without testing for ZnT8A). Screening for IA‐2A and ZnT8A alone allows identification of the majority of rapidly progressing prediabetic siblings and offspring regardless of age and is more cost‐effective to select participants for intervention trials than conventional screening.